The morphology of human hyoid bone in relation to sex, age and body proportions - Urbanová, P; Hejna, P; Zátopková, L; Šafr, M (Homo, 2013)
Morphological aspects of the human hyoid bone are, like many other skeletal elements in human body, greatly affected by individual's sex, age and body proportions. Still, the known sex-dependent bimodality of a number of body size characteristics overshadows the true within-group patterns. Given the ambiguity of the causal effects of age, sex and body size upon hyoid morphology the present study puts the relationship between shape of human hyoid bone and body proportions (height and weight) under scrutiny of a morphological study. Using 211 hyoid bones and landmark-based methods of geometric morphometrics, it was shown that the size of hyoid bones correlated positively with measured body dimensions but showed no correlation if the individual's sex was controlled for. For shape variables, our results revealed that hyoid morphology is clearly related to body size as expressed in terms of the height and weight. Yet, the hyoid shape was shown to result primarily from the sex-related bimodal distribution of studied body size descriptors which, in the case of the height-dependent model, exhibited opposite trends for males and females. Apart from the global hyoid shape given by spatial arrangements of the greater horns, body size dependency was translated into size and position of the hyoid body. None of the body size characters had any impact on hyoid asymmetry. Ultimately, sexually dimorphic variation was revealed for age-dependent changes in both size and shape of hyoid bones as male hyoids tend to be more susceptible to modifications with age than female bones.
Keywords: Analysis of Variance; dospělí; velikost těla; Female; Age Factors; Adult; ženské pohlaví; věkové faktory; lidé; Body Size; referenční hodnoty; Sex Characteristics; Hyoid Bone; analýza rozptylu; Male; Aged; Reference Values; pohlavní dimorfismus; os hyoideum; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Humans